Quantitative valve motion assessment in adolescents using point-of-care ultrasound: short communication - Riera, Antonio; Chen, Lei; Wright, Donald S.; Leviter, Julie I. (The Ultrasound Journal, 2025)
E-point septal separation (EPSS) and tricuspid annular plane systolic excursion (TAPSE) are M-mode measures of left and right ventricular systolic function, with limited pediatric point-of-care ultrasound (POCUS) research. We conducted a cross-sectional study in a pediatric emergency department, enrolling 12–17-year-olds without cardiopulmonary complaints. Exclusion criteria included abnormal vital signs, fever, altered mental status, or psychiatric illness. POCUS faculty performed the measurements, while blinded to pediatric echocardiography reference values. Data was analyzed using unpaired t-tests and Pearson’s correlation. Correlations with age, height, weight, body mass index, and heart rate were examined. Twenty subjects were enrolled. The mean EPSS was 2.5 mm (SD 1.9 mm), and the mean TAPSE was 2.6 cm (SD 0.4 cm), aligning with pediatric echocardiography reference values. No significant correlations were found between EPSS or TAPSE and anthropometric data.